2017
DOI: 10.3390/ijms18030487
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Cancer-Induced Neutrophil Extracellular Traps: A Potential Contributor to Cancer-Associated Thrombosis

Abstract: Pancreatic cancer (PaCa) is a highly metastatic cancer, and patients are at high risk of developing venous thromboembolism (VTE). Neutrophil extracellular traps (NETs) have been associated with cancer metastasis and cancer-associated thrombosis, but the ability of cancer to stimulate NET release is not known. The release of NETs has been shown to be a slow process and requires reactive oxygen species (ROS) production. Studies suggest that activated platelets are important mediators in the release. Here, we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(84 citation statements)
references
References 62 publications
3
74
0
Order By: Relevance
“…Cancer cells and cancer-activated platelets also induce NETosis. Pancreatic cancer cells were demonstrated to induce reactive oxygen species-independent NETosis after 30 min of incubation with neutrophils (68). Platelets that are primed by pancreatic cancer cells induce NETosis compared with control platelets (68).…”
Section: Cancer Progression and Cancer-associated Thrombosismentioning
confidence: 99%
“…Cancer cells and cancer-activated platelets also induce NETosis. Pancreatic cancer cells were demonstrated to induce reactive oxygen species-independent NETosis after 30 min of incubation with neutrophils (68). Platelets that are primed by pancreatic cancer cells induce NETosis compared with control platelets (68).…”
Section: Cancer Progression and Cancer-associated Thrombosismentioning
confidence: 99%
“…The disturbance between NET formation and clearance has thus been implicated in a number of various diseases, both systemic and limited to a certain organ or tissue. For example, excessive formation of NETs contributes to the pathogenesis of psoriasis, systemic lupus erythematosus, diabetes, cystic fibrosis, and cancer [13][14][15][16][17]. As mentioned above, it has been also recognized that NETs can be implicated in brain disorders and other pathological conditions affecting the CNS.…”
mentioning
confidence: 99%
“…Furthermore, IL-1β promotes further platelet activation in an autocrine manner by signaling via the IL-1R on platelets (32). Moreover, platelets constitute a major source of transforming growth factor (TGF)-β in the circulation (33). Enhanced platelet activation results in increased release of TGF-β, which can promote tumorigenesis in different ways.…”
Section: Secretion Of Pro-inflammatory Factors From Platelets Contribmentioning
confidence: 99%
“…If platelets play a role also in tumor-induced NET formation is currently not known, but not unlikely considering the elevated platelet activation in individuals with cancer. It was recently suggested that platelets prime tumor cells to promote NET formation (33). The authors suggest that this effect is due to platelets acting as carriers of tumor-derived exosomes, which in turn promote NET generation.…”
Section: Secretion Of Pro-inflammatory Factors From Platelets Contribmentioning
confidence: 99%